2015
DOI: 10.1097/fpc.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequence-based screening of TPMT variants in the Korean population

Abstract: Thiopurine S-methyltransferase (TPMT) is a cytoplasmic enzyme involved in the metabolism of thiopurine drugs and its activity is largely influenced by polymorphisms of the TPMT gene. To date, more than 35 TPMT variants are known to be associated with reduced enzyme activity, but most studies on the TPMT genotype have included only common nonfunctional variants, such as TPMT*2 and TPMT*3. In this study, we carried out a complete sequencing analysis to screen all TPMT variants in Korean patients. A total of 900 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 15 publications
(24 reference statements)
1
30
0
Order By: Relevance
“…Thus, common alleles can be preferentially selected to perform TPMT genotyping [86]. The TPMT * 3 has the highest prevalence (0.8–2.5%) in the Korean population, but the presence of * 6 , * 16 , * 32 , and * 38 has been reported [87]. The TPMT phenotypes based on each genotype are described in Table 6.…”
Section: Guidelines Per Genementioning
confidence: 99%
“…Thus, common alleles can be preferentially selected to perform TPMT genotyping [86]. The TPMT * 3 has the highest prevalence (0.8–2.5%) in the Korean population, but the presence of * 6 , * 16 , * 32 , and * 38 has been reported [87]. The TPMT phenotypes based on each genotype are described in Table 6.…”
Section: Guidelines Per Genementioning
confidence: 99%
“…For instance, most of the presented studies inferred TPMT activity by genotyping the most common nonfunctional TPMT alleles while results of a recent study that explored the sequencing data suggest that in certain populations, the inferred activity can be refined by incorporating the genotypes of other alleles. The study also identified a new variant in the TPMT gene, TPMT*38 (T514C), which had an allelic frequency of 0.11% and was predicted to be a damaging mutation 15. Moreover, as increasingly reported by different studies, genetic variants in other genes involved in thiopurines metabolism like ITPA, HGPRT and MTHFR as well as variants in genes independent of TPMT can influence thiopurines treatment outcome 14,20,25,41,70,77.…”
Section: Cost-effectivenessmentioning
confidence: 73%
“…TPMT deficiency was first described around 3 decades ago and it is currently well established that homozygous or compound heterozygous carriers of TPMT-deficient alleles have a significantly higher risk of early severe myelosuppression than patients homozygous for the wild-type 14,15. Patients with absent or reduced TPMT activity accumulate high doses of 6-TGNs, resulting in thiopurine-induced myelotoxicity that is characterized by early onset of severe neutropenia when such patients are treated with standard doses of thiopurine drugs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations